The neuropsychiatry of inborn errors of metabolism. Issue 4 (23rd May 2013) - Walterfang, Mark; Bonnot, Olivier; Mocellin, Ramon; Velakoulis, Dennis
Abstract: A number of metabolic disorders that affect the central nervous system can present in childhood, adolescence or adulthood as a phenocopy of a major psychiatric syndrome such as psychosis, depression, anxiety or mania. An understanding and awareness of secondary syndromes in metabolic disorders is of great importance as it can lead to the early diagnosis of such disorders. Many of these metabolic disorders are progressive and may have illness‐modifying treatments available. Earlier diagnosis may prevent or delay damage to the central nervous system and allow for the institution of appropriate treatment and family and genetic counselling. Metabolic disorders appear to result in neuropsychiatric illness either through disruption of late neurodevelopmental processes (metachromatic leukodystrophy, adrenoleukodystrophy, GM2 gangliosidosis, Niemann‐Pick type C, cerebrotendinous xanthomatosis, neuronal ceroid lipofuscinosis, and alpha mannosidosis) or via chronic or acute disruption of excitatory/inhibitory or monoaminergic neurotransmitter systems (acute intermittent porphyria, maple syrup urine disease, urea cycle disorders, phenylketonuria and disorders of homocysteine metabolism). In this manuscript we review the evidence for neuropsychiatric illness in major metabolic disorders and discuss the possible models for how these disorders result in psychiatric symptoms. Treatment considerations are discussed, including treatment resistance, the increased propensity for side‐effects and the possibility of some treatments worsening the underlying disorder.